Mathematics subject by the point of view of students - Saldauskienė, Jovita (Lietuvos matematikos rinkinys, 2008)
Actual mathematics subject problems at Vilnius College in Higher Education from not only the point of view of a teacher but also from the point of view of a student are analyzed there. The analysis shows the further ways for mathematics subject quality improvement.